Heavy Metals in Cassava (Manihot esculenta Crantz) Harvested from Farmlands along Highways in Owerri, Nigeria - Josephat Nwabueze Okereke; Judith Nkeiru Nduka; Ukaoma Augustina Adanma; Odangowei Inetiminebi Ogidi (Turkish Journal of Agriculture: Food Science and Technology)
Concentrations of heavy metals (Cu, Pb, Zn, Ni, Cd) in cassava grown on farmlands along highways in Owerri, was investigated. Cassava leaves and root samples were harvested from cassava farms along three major roads with high traffic density and another rural road that served as control location. Standard laboratory procedures to determine the concentration of these metals were adopted using Atomic Absorption Spectrophotometer. The metal concentrations in mg/kg in cassava root showed high levels of Cu (6.29±0.0346), Zn (8.49±2.243), Pb (0.5267±0.3156) and Cd (0.1167±0.0833). The concentrations of the heavy metals in the cassava leaves were of the order: Zn > Cu >Pb> Ni > Cd. Soil plant transfer factor values for all the metals in all the sites indicated medium accumulation. Heavy metal concentrations in soil showed significant correlation with concentrations in cassava root with no significant statistical differences in bioaccumulation of heavy metals in different parts of cassava. The overall results showed evidence of some heavy metal pollution on the soils and cassava plant.